Glaucoma management after corneal transplantation surgeries - Kornmann, Helen L. (Curr Opin Ophthalmol, 2016)
PURPOSE OF REVIEW: Intraocular pressure (IOP) elevation and glaucoma progression following corneal transplantation, specifically, penetrating keratoplasty, Descemet’s stripping endothelial keratoplasty, and Boston keratoprosthesis, are well described causes of ocular morbidity. Depending on the procedure performed, the incidence of glaucoma is highly variable. Several etiologic factors have been identified, the most common being synechial angle closure and corticosteroid-induced IOP elevation. The purpose of this review is to describe the various treatment strategies for glaucoma following corneal transplantation. RECENT FINDINGS: Medications and laser treatments are usually first-line therapies for postoperative IOP elevation. Surgical intervention, including filtering surgery and glaucoma drainage devices, may be necessary to control IOP and prevent progressive glaucomatous damage. SUMMARY: Glaucoma is a common complication of corneal transplantation, and the degree of aggressiveness is often related to the indication for corneal surgery. Although postoperative IOP elevation may be controlled with medical therapy alone, refractory cases may require glaucoma surgery. In all cases, early detection and intervention are necessary to optimize patient outcomes.